2018
DOI: 10.3389/fmicb.2018.00426
|View full text |Cite
|
Sign up to set email alerts
|

PlMAPK10, a Mitogen-Activated Protein Kinase (MAPK) in Peronophythora litchii, Is Required for Mycelial Growth, Sporulation, Laccase Activity, and Plant Infection

Abstract: Mitogen-activated protein kinase (MAPK) pathways are ubiquitous and evolutionarily conserved signal transduction modules directing cellular respond to a diverse array of stimuli, in the eukaryotic organisms. In this study, PlMAPK10 was identified to encode a MAPK in Peronophythora litchii, the oomycete pathogen causing litchi downy blight disease. PlMAPK10, containing a specific and highly conserved dual phosphorylation lip sequence SEY (Serine-Glutamic-Tyrosine), represents a novel group of MAPKs as previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…As a hemibiotrophic pathogen, P. litchii undergoes biotrophic and necrotrophic phases during infection. However, fewer studies have been conducted on the functions of P. litchii genes, hence there is scarcity of information about its pathogenesis and the litchi-P. litchii interaction mechanisms (Jiang et al, , 2018Kong et al, 2019). The identification and/or investigation of RXLR effectors in P. litchii lags behind that for other Phytophthora and downy mildew species, with only bioinformatics prediction of 245 putative RXLR effector genes (Ye et al, 2016).…”
mentioning
confidence: 99%
“…As a hemibiotrophic pathogen, P. litchii undergoes biotrophic and necrotrophic phases during infection. However, fewer studies have been conducted on the functions of P. litchii genes, hence there is scarcity of information about its pathogenesis and the litchi-P. litchii interaction mechanisms (Jiang et al, , 2018Kong et al, 2019). The identification and/or investigation of RXLR effectors in P. litchii lags behind that for other Phytophthora and downy mildew species, with only bioinformatics prediction of 245 putative RXLR effector genes (Ye et al, 2016).…”
mentioning
confidence: 99%
“…However, the function of MAPKs in development and pathogenicity of oomycetes are rarely known. In oomycetes, PsMAPK1, PsSAK1, PsMPK7 and MAPK10 showed various functions in vegetative growth, zoospore viability, stress tolerance, detoxification of reactive oxygen species, cyst germination, sexual reproduction, laccase activity and pathogenicity [10][11][12][13]. In this study, we identified the PlMAPK2 and found that its orthologs in oomycete are functional unknown MAPKs.…”
Section: Discussionmentioning
confidence: 77%
“…We further examined the transcriptional levels of 8 laccase-encoding genes found that 3 of them, Pl104952, Pl106183 and Pl111417, were dramatically down-reg in PlMAPK2 mutants, while Pl103272 and Pl106923 were slightly up-regulat In fungi, laccases participate in the oxidation of antibiotics such as flavonoids and phytoalexins and contribute to the virulence of pathogen [17]. In oomycetes, the laccase activity is also associated with the plant infection [5,10,18]. Here we tested the laccase activity of PlMAPK2 mutants and found that these mutants showed decreased laccase activity (Figure 7A).…”
Section: Plmapk2 Is Required For Full Virulence and Regulates Laccasementioning
confidence: 99%
See 2 more Smart Citations